Hedonic Behavior In The Use Of E-Money: An Experimental Study On Students Of The Faculty Of Economics At Private Universities In Palembang City - Angka Wijaya; Hadli Hadli; Daddyan Ariev Imantha; Naura Ilgalia Putri (UNIVED Press, 2026)
This study was motivated by the increasing intensity of e-money use among students. Although e-money provides convenience in transactions, this condition also encourages the emergence of uncontrolled consumptive behavior financially. This study observes variables such as hedonistic behavior, personal financial literacy, and intensity of e-money use. The population in this study consisted of active students of the Faculty of Economics at a private university in Palembang in 2025, with a sample size of 361 respondents. The results show that the intensity of e-money usage does not affect hedonistic behavior, and personal financial literacy also does not affect hedonistic behavior. However, personal financial literacy significantly affects the intensity of e-money usage. These findings emphasize the importance of personal financial literacy in moderating e-money usage, which can help students manage their finances more wisely despite the increasing ease of digital transactions.